EFFECT OF THE ADMINISTRATION OF ALOE VERA GEL EXTRACT ON THE HEALING TIME OF NIPPLE WOUND IN BREASTFEEDING MOTHERS. - Meti Widiya Lestari; Camelia Ratna Juwita; Uly Artha Silalahi (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
The benefits of breast milk are so great, but not many mothers are willing to give exclusive breastfeeding. Problems that often occur in breastfeeding mothers are improper breastfeeding techniques resulting in nipple wound. One of the non-pharmacological efforts to deal with wound nipples is aloe vera. Aloe vera is a plant that has been studied to accelerate wound healing. The purpose of this study was to determine the effect of the administration of aloe vera gel extract on the healing time of nipple wound in breastfeeding mothers. The research design used was quasi-experimental with a post-test only non equivalent control group study design. The sampling technique used was accidental sampling with a sample of 50 postpartum mothers divided into a control group and an experimental group. Analysis of statistical tests used by Chi Square. The results of the study were 23 people in the control group included in the normal category, while in the experimental group 22 people were included in the fast healing category.. The results of statistical tests obtained a value of p value of 0,000. The conclusion is the effect of aloe vera gel on the healing time of blisters nipples.